Gender in Global Politics - Ogunbanjo, M. 'Bimbo (NIU Journal of Humanities, 2021)
Gender refers, most basically, to the social construction of sexual difference. As such, ‘gender’ is clearly distinct from ‘sex’ (terms that are often used interchangeably in everyday language). For most feminists, ‘sex’ highlights biological, and therefore ineradicable, differences between females and males, while ‘gender’ denotes a set of culturally defined distinctions between women and men. This paper grapples with the way in which gender helps to structure global politics. It does so using feminist perspectives on International Relations ( IR ). It begins with a robust analysis of varieties of feminism, gives an overview of feminist theories more generally, and offers a feminist definition of gender. Feminists define gender as an unequal structural relationship of power. Building on a variety of the IR theoretical perspectives, IR feminists use gender to help them apprehend and comprehend why women are disadvantaged relative to men in all societies. The paper focuses on feminist perspectives on nation-states, security and the global economy. It scrutinizes gendered states and gendered nations, and stresses that the issues of identity in global politics are generally dominated by an emphasis on identification with the nation-state. The paper dilates on the masculinity of war and national security, suggesting that states’ national security policies are often legitimated in terms of masculine characteristics. This helps in the understanding why women have been so underrepresented in powerful positions in the international policy world and in militaries. Feminists consider the security of individuals to be as important as the security of states. There is an examination of how gendered economic structures of inequality, associated with a global gendered division of labour, can help in the explanation of why the majority of the world’s poor are women. The paper concludes by outlining some policy practices that are helping to lessen gender inequality. Keywords : Gender, Feminist, Global Politics, Security, Policy Practice, Social Constructivism